Effect of Smoking on the Progression and Severity of COVID-19 Infection among Adult Males in Sullia Taluk of Dakshina Kannada - Christa Jose; Nusrath Fareed; P. K. Asmin; Hemanth Battur; Jaseela Praveena (Wolters Kluwer Medknow Publications, 2024)
Context Coronavirus disease 2019 (COVID-19) primarily targets pulmonary epithelial cells, causing viral pneumonia and acute respiratory distress syndrome. It progresses more severely in chronic obstructive pulmonary disease patients. Aims The aim of the study was to assess the effects of smoking on the progression of COVID-19 infection among adult males in Sullia Taluk, Dakshina Kannada. Subjects and Methods A cross-sectional study was carried out among 230 male subjects, aged 18 years and above diagnosed with COVID-19 from the records of the general hospital, Sullia. Necessary data were collected using a validated questionnaire comprised of three parts, Part A recorded basic demography, Part B recorded details of smoking history, and Part C recorded details of COVID-19 symptomatology. Descriptive measures and Chi-square tests were conducted separately for each variable to determine the association between various determinants of smoking and COVID-19. P < 0.05 was considered statistically significant. Results The response rate of the study was 68.7%. Among the studied population, 20.3% were smokers. Analysis revealed that loss of taste or smell (73.91%), cough (52.17%), difficulty in breathing (52.17%), persistent pain in the chest (21.73%), and running nose (13.16%) were significantly higher among smokers compared to their nonsmoking counterparts. Conclusions Results of the study support the hypothesis that smoking has an effect on the progression and severity of COVID-19 infection.